1985
DOI: 10.1161/01.res.57.5.781
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide generation and reversal of acetylcholine-induced cerebral arteriolar dilation after acute hypertension.

Abstract: The appearance of superoxide anion radical in cerebral extracellular space during and after acute hypertension induced by intravenous norepinephrine was investigated in anesthetized cats equipped with cranial windows. Superoxide was detected by demonstrating the presence of superoxide dismutase-inhibitable reduction of nitroblue tetrazolium. The superoxide dismutase-inhibitable rate of reduction of nitroblue tetrazolium was 4.1 +/- 1.61 nM/min per cm2 during hypertension and 4.55 +/- 0.62 nM/min per cm2 one ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
94
4
2

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(103 citation statements)
references
References 30 publications
3
94
4
2
Order By: Relevance
“…However, oxygen-derived free radicals have been suggested to participate in the pathogenesis of hypertensive vascular disease by increasing vascular permeability and contractility as well as by inducing cellular injury, the interpretation of which is based on the inhibitory effects of free radical scavengers. [11][12][13]40 The biological effects seen with oxygen-derived free radicals noted above also occur with ChOx.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, oxygen-derived free radicals have been suggested to participate in the pathogenesis of hypertensive vascular disease by increasing vascular permeability and contractility as well as by inducing cellular injury, the interpretation of which is based on the inhibitory effects of free radical scavengers. [11][12][13]40 The biological effects seen with oxygen-derived free radicals noted above also occur with ChOx.…”
Section: Discussionmentioning
confidence: 95%
“…[7][8][9][10] However, only limited information concerning peroxidative processes in hypertension and their modification by antioxidants is available. [11][12][13][14][15][16] Because cholesterol oxides (ChOx) have been ubiquitously identified in human plasma and atheromatous lesions, their involvement in the atherogenic process is receiving increasing scrutiny. [17][18][19][20][21] ChOx may influence the atherogenic process in several ways, since they are cytotoxic toward the cellular components of the arterial wall, [22][23][24] increase vascular permeability, 25 promote cholesterol ester formation and accumulation, 26 -28 inhibit prostaglandin I 2 synthesis by endothelial cells, 29 and perturb cholesterol biosynthesis.…”
mentioning
confidence: 99%
“…Moreover, they would have found extensive evidence to support the hypothesis that vitamin C exerts certain effects because it is an antioxidant, as illustrated in my review on the possible role of oxidative stress in hypertension, published in 1993. 11 In fact, my studies showed that the same effect observed with vitamin C can be reproduced with 2 other antioxidants, thiopronine and glutathione, respectively. 9,10 The question of missing citations is surely an important one, and particularly so when the paternity of a finding or concept of some value is to be attributed.…”
Section: Jan Kyst Madsen MD Phdmentioning
confidence: 79%
“…We used cerebral pial arteries that have BBB properties [1,26] to investigate changes in permeability in response to ovariectomy and estrogen replacement in vitro. In cerebral endothelium that comprised the BBB, transcellular transport is low under normal conditions, but increases substantially under pathologic conditions in which barrier permeability is enhanced leading to vasogenic edema [19,34,50]. One of the earliest microscopic findings in an experimental animal model of acute hypertension (i.e., hypertensive encephalopathy) is an increased rate of pinocytosis in the cerebrovascular endothelium of arteries and arterioles, which allows significant passage of fluid and molecules into the brain [19,34].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen is a known antioxidant [15,32,33] and has been reported to inhibit membrane lipid peroxidation [2], thereby possibly attenuating the increased BBB permeability caused by free radical generation that is known to occur during acute hypertension and other brain injuries [41,50]. However, given that the level of estrogen in the OVX+E group was greater than CTL, estrogen replacement would be expected in this case to have a greater antioxidant effect and restore permeability to control levels.…”
Section: Discussionmentioning
confidence: 99%